Wear resistance of experimental titanium alloys for dental applications - Lapria Faria, Adriana Claudia; Silveira Rodrigues, Renata Cristina; Rosifini Alves Claro, Ana Paula [UNESP]; Chiarello de Mattos, Maria da Gloria; Ribeiro, Ricardo Faria (Elsevier B.V., 2011)
The present study evaluated microstructure, microhardness and wear resistance of experimental titanium alloys containing zirconium and tantalum. Alloys were melted in arc melting furnace according to the following compositions: Ti-5Zr, Ti-5Ta and Ti-5Ta-5Zr (%wt). Hemispheres and disks were obtained from wax patterns that were invested and cast by plasma. Microstructures were evaluated using optical microscopy and X-ray diffraction (XRD) analysis and also Vickers microhardness was measured. Hemispherical samples and disks were used for 2-body wear tests, performed by repeated grinding of the samples. Wear resistance was assessed as height loss after 40,000 cycles. The data were compared using ANOVA and post-hoc Tukey test. Ti-5Zr presented a Widmanstatten structure and the identified phases were alpha and alpha' while Ti-5Ta and Ti-5Ta-5Zr presented alpha, beta, alpha' and alpha '' phases, but the former presented a lamellar structure, and the other, acicular. The microhardness of Ti-5Zr was significantly greater than other materials and cp Ti presented wear resistance significantly lower than experimental alloys. It was concluded that wear resistance was improved when adding Ta and Zr to titanium and Zr increased microhardness of Ti-5Zr alloy. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Sliding wear; Titanium alloys; Dental applications; Two-body abrasion; Wear testing; Hardness tests